Torque steadiness and muscle activation are bilaterally impaired during shoulder abduction and flexion in chronic post-stroke subjects (2016)
Objective To characterize sensorimotor control and muscle activation in the shoulder of chronic hemiparetic during abduction and flexion in maximal and submaximal isometric contractions. Furthermore, to correlate submaximal sensorimotor control with motor impairment and degree of shoulder subluxation. Methods Thirteen chronic hemiparetic post-stroke age-gender matched with healthy were included. Isometric torques were assessed using a dynamometer. Electromyographic activity of the anterior and middle deltoid, upper trapezius, pectoralis major and serratus anterior muscles were collected. Variables were calculated for torque: peak, time to target, standard deviation (SD), coefficient of variation (CV), and standard error (RMSE); for muscle activity: maximum and minimum values, range and coefficient of activation. Motor impairment was determined by Fugl-Meyer and shoulder subluxation was measured with a caliper. Results Paretic and non-paretic limbs reduced peak and muscle activation during maximal isometric contraction. Paretic limb generated lower force when compared with non-paretic and control. Paretic and non-paretic presented higher values of SD, CV, RMSE, and CV for prime mover muscles and minimum values for all muscles during steadiness. No correlation was found between sensorimotor control, motor impairment and shoulder subluxation. Conclusion Chronic hemiparetic presented bilateral deficits in sensorimotor and muscle control during maximal and submaximal shoulder abduction and flexion. © 2016 Elsevier Ltd